Biochemical and cellular characterization of transcription factors binding to the hyperconserved core promoter-associated M4 motif. (December 2016) - Trung, Ngo; Kremmer, Elisabeth; Mittler, Gerhard
Abstract Background The motif ACTAYRNNNCCCR (Y being C or T, R being A or G, and N any nucleotide), called M4, was discovered as a putative cis-regulatory element, present 520 times in human promoter regions. Of these, 317 (61 %) are conserved within promoter sequences of four related organisms: human, mouse, rat, and dog. Recent genome-wide studies have described M4 as a transcription factor (TF) binding site for THAP11 that does often overlap with SBS (STAF Binding Site) a second core-promoter associated TF binding module, which associates with the TFs STAF/ZNF143 and RBP-J. Human M4-promoter genes show enhanced expression in cells of hematopoietic origin, especially in B lymphoblasts and peripheral blood B and T cells. Apart from RBP-J that is well known to recruit ICN1 (the intracellular transcriptional mediator of activated Notch1), the functional role of the hyperconserved M4 cis-element in the context of transcriptional regulation of M4-genes in lymphoid cells remains poorly defined. Results Here, we present a quantitative proteomic investigation of the M4 motif TF binding landscape in lymphoid cell lines that is further validated by ChIP experiments and functional assays. Our data strongly suggest that THAP11 and Ikaros interact directly, while NFKB1 (NF-kappa B p50) and HCF-1 are binding indirectly to M4-promoters in vitro and in living cells. Further analysis reveals that M4 is a bipartite composite cis-element, which is recognized by THAP11 via binding to the ACTAYR sequence module, thereby promoting ternary complex formation with HCF-1. Similarly, Ikaros binds to the CCCR module of the M4 motif and this interaction is crucial for recruiting NFKB1 to M4 harboring genes. Transient reporter assays in HEK293 and loss-of-function experiments in Molt4 T cells unequivocally demonstrate that binding of Ikaros and/or THAP11 to M4 bearing promoters is functionally important and therefore biologically relevant. Accordingly, this study validates our SILAC-based DNA protein interaction screening methodology as a valuable surrogate for a bona fide reverse ChIP technology. Conclusions The M4 motif (ACTAYRNNNCCCR) is a functional regulatory bipartite cis-element, which engages a THAP11/HCF-1 complex via binding to the ACTAYR module, while the CCCRRNRNRC subsequence part constitutes a binding platform for Ikaros and NFKB1.